2013
DOI: 10.1016/j.pmrj.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Shunted Hydrocephalus Has a Significant Impact on Quality of Life in Children With Spina Bifida

Abstract: Shunted hydrocephalus has a negative impact on the perception of quality of life, an effect that may be attenuated by age. Further study and more-specific measurement tools are needed to better understand health-related quality of life in children with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
2
17
1
1
Order By: Relevance
“…In contrast, five small sample studies ( n =31–68) did not find a correlation between age and QOL (Cate et al ; Padua et al ; Oddson et al ; MacNeily et al ; Okurowska‐Zawada et al ). Furthermore, two other small sample studies (Muller‐Godeffroy et al ; Ramachandra et al ) have found that older children reported even less impact of their condition on HRQOL.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, five small sample studies ( n =31–68) did not find a correlation between age and QOL (Cate et al ; Padua et al ; Oddson et al ; MacNeily et al ; Okurowska‐Zawada et al ). Furthermore, two other small sample studies (Muller‐Godeffroy et al ; Ramachandra et al ) have found that older children reported even less impact of their condition on HRQOL.…”
Section: Resultsmentioning
confidence: 97%
“…The PedsQL child and parent formats were the most frequently used generic instruments in children. Nearly all of the studies that used the PedsQL found lower scores on all scales in the MMC children group as compared with the reference samples of healthy children (Oddson et al ; Abresch et al ; Flanagan et al ; Sumpter et al, ; Johansen et al ; Freeman et al ; Olesen et al ; Ramachandra et al ; Wide et al ; Murray et al ). The greatest reduction in HRQOL was found in physical functioning and the smallest one was in emotional functioning (Oddson et al ; Abresch et al, ; Sumpter et al ; Johansen et al ; Freeman et al ).…”
Section: Resultsmentioning
confidence: 98%
“…In studies with children and their caregivers, some researchers have noted that poor HRQOL is clinically related to lesion level, age, ambulatory ability, family function, and rehabilitation treatment team integration. 9,12,14,18,20,22,23,25 Meanwhile, other studies have noted that HRQOL in spina bifida patients is unrelated to age, functional ability, lesion level, sex, obesity, or sexual function. 1,8,13,14,15,20 Our investigation of several variables that were applicable to the entire clinic population found none that correlated with HRQOL score.…”
Section: Effect Of Demographic Variablesmentioning
confidence: 99%
“…20,22 As such, the importance of studying health-related quality of life (HRQOL) in addition to traditional outcome measures in the spina bifida population is being increasingly recognized. 18 HRQOL focuses on how each patient assesses the influence of a chronic health issue on his/her physical and psychosocial functioning. 17,21 The goal of the present study was to characterize the quality of life (QOL) of pediatric patients with spina bifida who were seen at a multidisciplinary, comprehensive outpatient clinic within a large medical center.…”
mentioning
confidence: 99%
“…A previous small study in San Diego9 found that shunted hydrocephalus was significantly associated with poorer self-reported physical health summary scores, but other studies have not replicated this finding 13 18. Hydrocephalus has been associated with increased functional dependence19 and poorer neurocognitive outcomes 20.…”
Section: Discussionmentioning
confidence: 94%